Prolonged P wave dispersion in patients with acute ischemic stroke - Altas, Yakup; Celik, Ahmet; Korkmaz, Hasan; Ali Kobat, Mehmet; Kurtoglu, Ertugrul; Yavuzkir, Mustafa Ferzeyn (My University, 2011)
The aim of this study is to show the prolonged P Wave Dispersion (PWD) in patients with acute ischemic stroke. Researchers compared PWD in patients with acute ischemic stroke (n = 50) with age-matched healthy subjects (n = 46) as controls. Twelve-lead electrocardiograms of all patients were obtained and PWDs were measured. Left ventricular diameters and functions were also obtained by transthoracic echocardiography. The demographic properties of the study population were similar between two groups. P wave dispersions were significantly longer in patients with acute ischemic stroke than control subjects (77±26 and 63±21 m sec, respectively p = 0.007). The left ventricular end-systolic, end-diastolic diameters and ejection fraction were similar between two groups. The interventricular septal diameter and left atrial diameter were significantly higher in patients with acute ischemic stroke than those in control group. This study demonstrates that prolonged PWD has a relationship with acute ischemic stroke. Prolonged PWD may be a predictor of ischemic stroke. © Medwell Journals, 2011.
Keywords: Cardiology; Ischemic stroke; P wave dispersion; Patients; Stroke; Turkey